Penerapan model PBL materi aplikasi gelombang elektromagnetik hasil analisis kontaminan daging menggunakan metode spektroskopi - Ria Aprilia (Pendipa, 2019)
ABSTRACT [Implementation PBL model in electromagnetic wave material from analysis result of meat contaminant with spectroscopy method]. The aims at this study was to explain differences in learning outcomes between students who study with Problem Based Learning Learning Model (PBL) with students who study conventionally on Electromagnetic Waves material. This method of educational research used quasi experimental research methods. The design of this research is pretest-posttest control group design. Population in this research is all class X SMA Negeri 9 Lubuklinggau, which consists of 4 classes and selected as sample is class X.1 as experiment class and X.2 as control class. Technique of collecting data used is test. The hypothesis of this study is that there are differences in learning outcomes between students learning to use Problem Based Learning (PBL) learning model with students who study conventionally in Physics learning at SMA Negeri 9 Lubuklinggau. Differences can be seen from the results of the mean values of the control and experimental classes, the control class has an average grade value of 80.09 and the experimental class has an average value of 87.25. Based on result of analysis obtained from t test, that is tcount bigger than ttable with value 4,64 > 1,68 then H0 refused and Ha accepted. Thus the hypothesis proposed in this study accepted the truth.